THE NOTION OF TERRORISM IN ROMANIAN CRIMINAL LAW - Sandra Sophie-Elise OLĂNESCU (Challenges of the Knowledge Society)
Terrorism is a complex phenomenon which describes some of the most serious criminal acts facing humanity, through the degree of social danger, the purpose and impact of its reprehensible consequences, both in terms of the territory affected and of the manner and means of its perpetration, as well as the significant number of potential/concrete victims. The contradictorily nature of terrorism, as an antisocial activity that disrupts national security, public order and peace, including the rudimentary normal life of various human communities – as a precursor to organized, state-type society – has put the conception of this destructive human behavior at the forefront of research. Thus, the difficulty of defining and conceptual boundary of terrorism from other prohibited acts is, in part, in various ideological interpretations, the current predisposition of political/state actors to give, when referred to, a diabolic connotation that increases the ambiguity and unclarity of this process. Romania has not been a stranger to normative proposals or formal provisions that prohibit criminal offenses that are currently legally classified as acts of terrorism, in which sense such acts have been regulated and punished since the second half of the 19th century. The purpose of this paper is to analyze the Romanian legal precursors of criminal rules banning and sanctioning terrorist offenses, to observe their beginnings, evolution, and any gaps or irregularities that may be corrected in the future.